2019
DOI: 10.1186/s12967-019-2072-3
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived exosomes (MDEs) have a different biological effect on normal fetal colon epithelial cells compared to colon tumor cells in a miRNA-dependent manner

Abstract: Background Breastfeeding is the ideal source of infant nutrition. Human milk consists not only of nutrients but also biologically active components. Among these latter compounds, exosomes contain proteins, lipids, mRNAs and miRNAs. Methods To elucidate the biological effects of milk-derived exosomes (MDEs) on normal colonic epithelial cells compared to colonic tumor cells, we incubated cells with MDEs. MDEs were able to enter into no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 39 publications
2
91
0
2
Order By: Relevance
“…Moreover, microRNA-148a and microRNA-21 inhibit DNA methyltransferase 1 (DNMT1) [68], an oncogene which is also overexpressed in CRC [69][70][71]. Indeed, incubation of CRC cells (Lim 1215) with human milk exosomes increased the cellular content of microRNA-148a [5], and addition of milk exosomes to normal intestinal cells (CRL 1831) significantly decreased DNMT1 expression [5,24]. Three large meta-analyses came to the conclusion that milk consumption but not the consumption of fermented milk products, where exosomal mi-croRNAs including microRNA-21 are depleted [52], has a protective effect against the development of CRC [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, microRNA-148a and microRNA-21 inhibit DNA methyltransferase 1 (DNMT1) [68], an oncogene which is also overexpressed in CRC [69][70][71]. Indeed, incubation of CRC cells (Lim 1215) with human milk exosomes increased the cellular content of microRNA-148a [5], and addition of milk exosomes to normal intestinal cells (CRL 1831) significantly decreased DNMT1 expression [5,24]. Three large meta-analyses came to the conclusion that milk consumption but not the consumption of fermented milk products, where exosomal mi-croRNAs including microRNA-21 are depleted [52], has a protective effect against the development of CRC [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Whether nonabsorbed exosomes also act from the luminal side is not elucidated. Recent evidence indicates that milk exosomes play a critical role for intestinal maturation and function in humans and rodent models [22][23][24][25][26][27][28]. It has been demonstrated in murine models that human, bovine, and porcine milk exosomes support intestinal cell growth [22][23][24], attenuate LPS-induced apoptosis [25], prevent intestinal endothelial cell damage [26,27], enhance goblet cell numbers and mucin production [28], modify bacterial growth, and promote intestinal microbiota [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubio et al identified miRNAs, piRNAs, tRNAs, snRNAs, and snoRNAs in milk/plasma centrifugation at 16,000 g for 15 minutes www.nature.com/scientificreports www.nature.com/scientificreports/ at 4 °C 55 . Herwijnen et al, collected sucrose gradient (1.12-1.18 g/ml) fractions from human and porcine milk showed abundant of let-7 family members and miR-148a 67 , a series of centrifugations and filtrations combination of ExoQuick regent for human milk exosome isolation was proofed that miRNA-148a is a highly expressed miRNA and down-regulated PTEN (phosphatase and tensin homolog) in normal fetal colon epithelial but not in colon tumor cells, and milk-derived exosomes deleted of miRNA-148a, which inhibited proliferation and DNMT1(DNA methyltransferase 1) expression in cells 68 . But a recently reported that unfractionated cow milk and derived EV subsets with differential ultracentrifugation 12,000 g (P12K), 35,000 g (P35K), 70,000 g (P70K), and 100,000 g (P100K) exhibited P100K EV were enriched in reference miRNA sequences, and P12K and P35K EV in related isomiR.…”
Section: Discussionmentioning
confidence: 99%
“…Reif et al reported that HBM-derived exosomes promote the proliferation of normal colon epithelial cells without affecting the growth of colonic cancer cells [ 80 ]. Although this study does not show the direct antitumor effects of human milk exosomes, it suggests the beneficial function of human milk exosomes through differential effects on normal cells compared to cancer cells.…”
Section: Breast Milk-derived Exosomesmentioning
confidence: 99%